2011
DOI: 10.1007/s11064-010-0378-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Glycometabolic Enzymes in Multi-infarct Dementia Rats

Abstract: Acupuncture has exhibited therapeutic effects on vascular dementia in our previous research. The mechanism of its anti-dementia effects involves energy metabolism. For brain cells, glucose metabolism is almost the only source of energy, and glucose metabolism disorders are early signs of dementia. In addition, glucose metabolism associates closely with glycometabolic enzymes, thereby maintains normal energy supply in brains and neurological and mental activities. In order to investigate its anti-dementia mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…All the studies stated the weight range of the rats, which ranged from 180 to 490 g. A total of 7 of the 16 studies mentioned the age of the animals [ 11 , 14 , 16 18 , 23 , 25 ], which ranged from 2 months old to 12 months old. Sixteen of the included studies used different subtests of the Morris water maze test; all the studies met the inclusion criteria by using escape latency as outcome data, while two studies used swimming speed [ 24 , 26 ], five studies used duration in the quadrant of the former platform position [ 12 , 13 , 21 , 24 , 26 ], one used swimming distance [ 19 ], and three used frequency of crossing former platform [ 12 , 15 , 16 ]. Two species of rats were used in the 16 studies: seven studies used Sprague–Dawley (SD) rats [ 11 , 13 , 15 , 17 19 , 25 ], and nine studies used Wistar rats [ 12 , 14 , 16 , 20 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies stated the weight range of the rats, which ranged from 180 to 490 g. A total of 7 of the 16 studies mentioned the age of the animals [ 11 , 14 , 16 18 , 23 , 25 ], which ranged from 2 months old to 12 months old. Sixteen of the included studies used different subtests of the Morris water maze test; all the studies met the inclusion criteria by using escape latency as outcome data, while two studies used swimming speed [ 24 , 26 ], five studies used duration in the quadrant of the former platform position [ 12 , 13 , 21 , 24 , 26 ], one used swimming distance [ 19 ], and three used frequency of crossing former platform [ 12 , 15 , 16 ]. Two species of rats were used in the 16 studies: seven studies used Sprague–Dawley (SD) rats [ 11 , 13 , 15 , 17 19 , 25 ], and nine studies used Wistar rats [ 12 , 14 , 16 , 20 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various methods were used to establish a vascular dementia (VD) model in the different studies (Table 1 ) [ 29 ]. The 4-vessel occlusion (4-VO) method was used in two studies [ 11 , 13 ]; 7 studies used bilateral common carotid artery occlusion (2-VO) [ 15 , 17 20 , 24 , 26 ]; 6 studies used embolic occlusion (EO) [ 12 , 14 , 16 , 21 24 ]; and the remaining trial used middle cerebral artery occlusion (MCAO) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the neuroprotective effect of acupuncture for VD rats in improving cognitive function [ 31 , 32 ], increasing glucose metabolism [ 23 ], reducing oxidative stress damage [ 22 , 25 , 33 ], and exerting anti-apoptotic effect [ 24 , 34 ]. Furthermore, our previous clinical trials suggested that acupuncture may be useful in relieving symptoms of VD to some extent [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…,故早期发现,早期鉴别,早期给 予干预治疗对老年痴呆的防治有非常重要意义 [5] 。笔者对该疾病采用的口服尼莫地平与脑心通联合针刺百会、四 神聪穴治疗研究,本文对该研究分析总结如下: [11] 。缺血性卒 中的发病率在中国以每年 8.7%的速度增长 [12] ,认知障碍是脑梗死后各危险因素、脑血管损害和遗传因素等共同 作用的结果 [13] ,早期发现脑血管危险因素,积极控制危险因素,阻止或逆转认知障碍的进展,这是我们盼望的。 但是其病因的复杂性及不明确性,加上痴呆患者不可逆性的病理,对 MCI 患者早期发现、早期干预治疗,就具 有非常重要意义。 MCI 的早期干预治疗包括去除和治疗病因,及早对患者及家属进行健康教育指导,开展心理疏导,还可给 各种训练如思维、作业、记忆、运动等。给予患者药物治疗是早期干预治疗中的关键,服用药物可改善患者的 脑组织血流,促进脑神经细胞代谢,如服用钙阻滞剂,中成药等。而其中钙阻滞剂尼莫地平是目前受到国内外 指南、共识和循证证据推荐的,是从血管角度唯一一种对认知障碍进行干预治疗的药物,改善认知功能很有效。 有最新的临床荟萃,尼莫地平对各种类型痴呆均有治疗作用,并且安全有效,可推广临床应用。 中医学"呆病"的轻证可用来解释轻度认知障碍。病机为年迈体虚,七情内伤,久病耗损,而致诸邪为疾 患,逐渐脑髓空虚,气血均亏,肾精耗损,痰瘀阻滞,脑髓失养。可选用针刺治疗,百会穴主治惊悸无心力以 及忘前失后等症 [14] ,故选用刺百会四神聪两穴。而有现代医学研究证明,针刺可诱导颞叶脑组织血流量和脑血流 容积的增加,对脑缺血损伤可对抗,可有效改善脑缺血区循环,保护脑神经元,改善脑神经细胞电活动的作用。 针刺由于其多途径、多靶点效应而在临床上广泛使用 [15] 。研究表明针刺 [16] 和康复训练能够改善脑卒中后认知障 碍,提高运动功能和日常生活活动能力。Lan Zhao [17] 等观察采用"益气调血,扶本培元"针刺法治疗多发性梗塞 所致血管性痴呆大鼠认知功能及对糖代谢的影响,结果发现针刺可以提高大鼠脑组织中己糖激酶、丙酮酸激酶、 磷酸葡萄糖脱氢酶的含量,这可能是针刺改善血管性痴呆的机制之一。张雪竹 [18] 等观察针刺对多发性梗塞痴呆 大鼠认知能力及脑组织葡萄糖转运的影响,结果发现针刺可以显著改善 MID 大鼠空间记忆能力、思维能力及分 析判断能力,促进海马葡萄糖转运蛋白 1 和 3 表达。提示调节脑血流,增强葡萄糖转运代谢可能"益气调血, 扶本培元"针法改善大鼠认知功能作用的作用机制之一。 脑心通胶囊是中药复方制剂,具有多种中药成份,包括黄芪、水蛭、地龙、全蝎、当归、川芎等,对心、 脑血管疾病具有益气活血、化瘀通脉的功效。 所以运用 MoCA 评估量表,早期筛查出 MCI,早期发现 MCI,给予针刺百会四神聪联合尼莫地平脑心通, 给予早期干预治疗,可以达到理想的效果,有效减少 MCI 的危害。能早期发现患者认知功能障碍并及时进行临 床干预,对改善患者的预后具有积极意义 [18] 。对于轻度认知障碍进行早期干预治疗,能及时延缓病情进展,可 减轻患者家庭以及社会的负担,取得事半功倍的效果。…”
unclassified